Americanization of election campaigns and the application of marketing on the political market in Poland in the first decade of political changes - Sempach, Marek (Koszty współczesnych kryzysów, 2021)
Since 1952 political marketing has been constantly developed in the US that became world’s leader in marketing application on political marketplace. After the collapse of communism in Poland in 1989 the new environmental circumstances arose and the American style political campaigning became attainable. This paper contains the evaluation of key polish campaigns that occurred within the first decade after the political transformation. It verifies the nature of marketing applied and local parties organization commitment certifying the issue of Americanization of polish marketing performance. Due to the to the analysis performed and sources criticism including the observation, the key question of Americanization degree of local parties marketing is confirmed.